Environmental protection in civil engineering with regard to the use of eco and nano materials - Petrović, Miloš Z.; Đorić-Veljković, Snežana M.; Karamarković, Jugoslav P. (Vojnotehnički glasnik / Military Technical Courier, 2014)
The looks of any environment, the identity of which is expressed through its form, structure and color, is one of the most significant characteristics of any area. The  first structures that catch the observer's eye are buildings and urban structures. People have always attached importance to the choice of building materials and interior design. Materials used have been specific for certain regions. In the era of modern technology and the expansion of new technical advances, the man and his environment require materials which are going to enrich living space, while constructions and shaped volumes will be made richer and more content aware. Materials should fulfill criteria which allow comfort, provide efficient energy consumption, healthy living conditions and preserve the environment. Buildings significantly change our environment. Most of such man-made objects do not comply with the needs of environmental protection because they are energetically inefficient, too cold or too hot and expensive to maintain. They are mostly built of materials which have a negative effect on health and environment. About 40% of stone and small and big aggregate are used for their production, as well as 25% of timber. Such objects waste 40% of energy and 16% of water worldwide. The use of eco-friendly materials  results in objects with a minimal influence on the environment and at the same time such materials are more economical and healthier for living. Environmental protection and construction means the maximum utilization of natural site conditions, usage of healthy materials,  efficient consumption of water and energy for building and use of water. In the process of European integration of Serbia, there is a harmonization of the national regulations regarding the environmental protection with the EU regulations. This process includes the transfer of a significant part of jurisdiction in this field to the local government level, including jobs which refer to global environmental problems. The influence of ecology is an important global issue. There is a huge pressure from many sides to minimize influence - requests often come from governments, trade associations and other social and financial stakeholders. The implementation of "ecologically eligible products", i.e. materials used in construction and consistent with the protection of the environment, is one of the first steps towards the realization of the concept of sustainable development and environmental protection. These materials are flexible, reliable, durable, and suitable for repeated use. Environmental compatibility of materials is of great importance in the context of the production of consumable resources. The focus of the production is to create wasteless methodologies that optimize production and maximize environmental performances. The basic features are: -          reduced amount of materials used, -          use of recycled materials, -          use of materials from the immediate environment, -          increased energy efficiency, -          increased longevity of the product, -          use of materials with less impact on the environment, -          reduced amount of waste, -          property of  re-recycling (recyclability), -          capable of measuring carbon footprint, and -          applied principles of sustainable development. The reduction of an environmental impact is also highlighted. This applies to the entire ecological life cycle, from raw material extraction to product disposal (clean production). Currently, the aim is to optimize the entire socio-economic system of the product, as well as to meet the criteria for sustainable development and environmental protection. Brick is the most widely used building material in the region. It is easily available, accepted and does not require additional education of contractors. It is very durable and resistant to moldering and insects. Because of its density, it warms more slowly in summer and in winter it  cools more slowly, which helps to maintain the temperature inside the object. Modern brick manufacturers have improved their production in order to pollute the environment less . Wood is the "greenest" material. If forests are kept regularly, trees will grow without violating a natural balance. Wooden structures can last for centuries without being damaged by the elements. That is, if they are properly protected from moisture, insects and unforeseen damage. It is biodegradable and it does not make any damage and negative effect on the environment. A relatively small amount of energy is needed so that wood can be processed and prepared for building, but wood requires regular constant maintenance and coating chemicals for protection. These coatings are expensive and anything but ecological and they have negative influence on the environment. Simprolit blocks have excellent sanitary - epidemiological characteristics. In objects built of Simprolit blocks, environmental requirements are completely fulfilled. Simprolit block walls are declared as "dry" (no more than 4% of moisture). In case of soaking, during great damage , such structures dry quickly without any loss of their physical characteristics. During floods, Simprolit block walls do not absorb moisture by means or capillary climbing like brick, siporex, foam concrete and other materials (in case of floods, walls of these materials absorb water along the entire height, and it takes time to dry , sometimes more than a year). In the class of lightweight concrete, Simprolit polystyrene is one of the lightest. Building facade and inner walls using Simprolit blocks significantly reduces the load on the structural elements of objects, reduces their dimensions and also reduces needed armature and weight, which directly impacts the construction f costs. Low emissivity glass is an important EKO material. Low emission glass or Low-E glass is a microscopic thin layer of a metal or metal oxide, which is applied on the glass by vapor deposition of a metal on a molecular level. Glass coated with a metal film only allows short wavelength radiation (visible part of the spectrum), while it reflects the long wavelength radiation (infrared rays) from the warm side of the glass onto the cold side. LOW-E blocks almost 98% of harmful sun rays, so in the cold period big glazed house rooms can become collectors of solar energy, so they can contribute to save precious heat. Glass which protects fromsun is made as a single glass surface or insulating glass. Its purpose is to keep back the solar energy which falls onto a glass surface. This glass does not have protection from glaring. A protective coating is applied on the inner side of the exterior glass. Self cleaning glass is hydrophilic and hydrophobic glass based on a “lotus effect”. A hydrophobic glass surface repells water and a hydrophilic one does the opposite. The development of bionics saw the usage of various effects occurring in many plants including a lotus leaf, i.e. a lotus effect. The leaves of the lotus cannot get wet, and after the rain they are dry and clean because water which slides down the leaves takes the dirt and dust, so the leaf stays clean. The droplets of water can pick up particles of dirt because the microstructure (namely, nanostructure) of a lotus leaf surface is such that minimises the adhesion of water droplets to the surface. Active Ceramic tiles are responsive to contaminants in the air, and turn them into non-toxic mineral salts. The tiles can be used both indoors as well as outdoors. This new invention is designed by dr. Romana Minozzija from Italy and his team. A group of scientists intended to "build a new tile that is not only aesthetically pleasing, but which also has a unique feature, play an active role in improving the quality of human life." Active ceramic plates are coated with a layer of titanium dioxide. When it is exposed to the light or when in humid environment, titanium dioxide activates and starts a chemical reaction. The process is called photocatalisis. Green and smart concrete are also materials used for building structures in civil engineering. Green concrete refers to various activities of efficient consumption of cement, whose production releases large amounts of carbon dioxide. In recent decades,modern civil engineering and environmental protection  face a problem correlated with the structure  and the protection of the environment, because the impact of some building materials can be harmful to human health and the environment as well. Materials in buildings, machinery and equipment can also contain very dangerous and harmful materials. Some of more affordable solutions are given in this paper together with the presentations of some ecological materials and the postulates of environmental protection.
Keywords: tree; blocks; glass; lotus; concrete; legal documents; tiles; bricks; environment; nano materials; eco materials